POVERTY ERADICATION AND NATIONAL DEVELOPMENT: AN APPRAISAL OF TELEVISION JINGLES - DORCAS BABA; AYODELE B. JOSEPH; MENDOS B. DOGO (International Studies Journal)
Poverty eradication remains a critical global goal, as reflected in the United Nations Sustainable Development Goals (SDGs), particularly Goal 1: No Poverty. Despite progress in reducing global poverty rates, significant challenges persist. This study therefore examines the role of television jingles in poverty eradication and national development. Drawing on the principle of Media Development theory, the study investigates the impact of television jingles on raising awareness about poverty, shaping public perceptions, and motivating behavioral change. Through a mixed-methods approach, including a literature review and conceptual review, the research demonstrates the significant influence of television jingles in addressing poverty-related issues. The results of this research emphasize how television jingles have a noteworthy effect on increasing awareness about poverty and rallying support for initiatives aimed at reducing it. With their persuasive abilities, television jingles can grab viewers' attention, influence their perspectives, and motivate them to take action in the fight against poverty. Suggestions for enhancing the impact of television jingles in poverty eradication and national development are provided. Policymakers should consider implementing supportive policies, including financial incentives and regulatory frameworks, to encourage the production and dissemination of socially impactful television jingles.